Què és (x ^ -3) ^ 2 * x ^ 5 / x ^ -1?

Què és (x ^ -3) ^ 2 * x ^ 5 / x ^ -1?
Anonim

Resposta:

1

Explicació:

(x ^ -3) ^ 2 * x ^ 5 / x ^ -1 = x ^ (- 3 * 2) * x ^ 5 * x ^ 1 = x ^ -6 * x ^ 6 = x ^ 6 / x ^ 6 = 1

Resposta:

1

Aplicar les lleis dels índexs

Explicació:

(x ^ -3) ^ 2 xx x ^ 5 / x ^ -1 "" larr (x ^ m) ^ n = x ^ (mn)

= x ^ -6 xx x ^ 5 / x ^ -1 "" larr x ^ -m = 1 / x ^ m

= 1 / x ^ 6 xx x 5 x 5 x 1 "larr x ^ m xx x ^ n = x ^ (m + n)

= x ^ 6 / x ^ 6

= x ^ 0 "" larr x ^ m / x ^ n = x ^ (m-n)

= 1 "" larr x ^ 0 = 1

Resposta:

color (magenta) (= 1

Explicació:

(x ^ (- 3)) ^ 2 x ^ 5 / x ^ (- 1

"Aplicant la llei:" color (blau) ((a ^ m) ^ n = a ^ (mn;

= x ^ (- 3xx2) x ^ 5 / x ^ (- 1

= x ^ (- 6) x ^ 5 / x ^ (- 1

"Aplicant la llei:" color (blau) (a ^ m / a ^ n = a ^ (m-n)

= x ^ (- 6) x ^ (5 - (- 1))

= x ^ -6 x ^ 6

"Aplicant la llei:" color (blau) (a ^ m a ^ n = a ^ (m + n); "

= x ^ (- 6 + 6)

= x ^ 0

"Aplicant la llei:" color (blau) (a ^ 0 = 1

color (magenta) (x ^ 0 = 1

-"Espero que això ajudi!:)"